Las que se quedan: Género, Migración y Control Social - Maria José Garcia Oramas; Susana Ruiz Pimentel; Sara Ruiz Vallejo (Les Cahiers ALHIM)
Migration impacts family structure, affecting both those who leave and those who stay, forcing all to confront a process of change and accommodation as a result of new realities. However, people are able to develop different strategies, more or less effective, allowing them to maintain their family bonds as well as to develop new networks of solidarity among the members of their communities. This is true for both sides of the frontier particularly in the case of coffee growing areas of central Veracruz, in the southeastern part of Mexico, where men typically migrate leaving women in care of the children and their households, under the tutelage of their relatives.  The absence of men in their communities -- (e.g., their husband, brothers, etc.) allows women to experience new forms of autonomy derived from the necessity of doing tasks and playing roles which normally belong to men, even if they do so under the control and vigilance of the community.  Also, they become closer to other women who live in similar situations and learn from each other to relate and help themselves in this hard process that can last years. Community media, like Radio Teocelo of Veracruz, transmitting in the area since more than 40 years, has represented an important collective vehicle promoting community development. In association with this radio, a group of researchers and students of the Psychology Faculty at the University of Veracruz, have designed a special radio program called: Women Voices from migration: the other side of the coin, in air from March 2010 to March 2011, as an strategy to promote women’s development giving them a voice to share and learn from one another’s experiences around migration.